THE UTILIZATION OF RIVERBANK AREAS AS TOURIST DESTINATIONS IN BANJARMASIN CITY - Jumriani, Jumriani; Arisanty, Deasy; Angriani, Parida (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lambung Mangkurat, 2024)
This article explores the potential for developing riverbank areas in Banjarmasin City into tourist destinations through a comprehensive literature review. Banjarmasin, known as the